Stem cell registry programme for patients with ischemic cardiomyopathy undergoing coronary artery bypass grafting: what benefits does it derive?. (19th February 2017) - Nesteruk, Julia; Voronina, Natalia; Kundt, Guenther; Donndorf, Peter; Klopsch, Christian; Kaminski, Alexander; Duckers, Henrick J.; Steinhoff, Gustav
Abstract: Aims: Standardization of stem cell therapy requires application of appropriate methods to evaluate safety and efficacy, including long‐term pharmacovigilance. To accomplish this objective, a long‐term registry programme was installed. Methods and results: We analysed 150 patients with ischemic cardiomyopathy, who received intramyocardial CD133+ bone marrow mononuclear stem cell treatment combined with coronary artery bypass grafting (CABG) or CABG alone. The mortality rate, major adverse cerebral and cardiac events, and functional outcome parameters were evaluated for the time period up to 14 years follow‐up. As a result, we have stratified the patient population (96 patients) into responders and non‐responders. Furthermore, the analysis of relevant predictors of good response to CD133+ bone marrow mononuclear stem cell treatment was performed. Several positive tendencies related to stem cells transplantation were demonstrated. First, no significant difference in major adverse cardiovascular and cerebral events was observed between stem cell and control group up to 14 years follow‐up. Second, an improvement of left ventricle ejection fraction (LVEF) in stem cell group retained for 5 years in contrast with CABG‐only group, where no significant changes in LVEF after 2 years were observed. In addition, LVEF under 30% and left ventricle end diastolic diameter above 60 mm were independent predictors of functional response to CD133+ cell therapy. Conclusions: Participants with overt heart failure benefit most from CABG combined with intramyocardial injection of CD133+ bone marrow mononuclear cell within the group. An improvement LVEF in stem cell group remained for 5 years in contrast with the CABG‐only group. The patients, in whom the improvement of both LVEF and LVED was observed, have benefited by increased life expectancy.